2019
DOI: 10.1093/milmed/usz001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 7 Months of Physical Training and Military Routine on the Bone Mass of Young Adults

Abstract: Introduction Physical activity (PA) has a great influence on bone mineral density (BMD) and bone mineral content (BMC), however longitudinal studies that seek to relate bone mass to physical activity are scarce and have a small sample size. The aim of this study was to evaluate and compare the effect of 7 months of military physical training (MPT), impact sports (IS), and swimming in the bone mass of young military adults. Materials and Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Some studies have indicated significant improvements in military personnel after undergoing MPT sessions in upper limbs endurance, corroborating that military training with an approximate duration of eight weeks promotes important adaptations in physical fitness (Campos et al, 2017;De Avila et al, 2013;El Hage & Reis Filho, 2013;Heinrich et al, 2012;Ojanen et al, 2020). Similar to the present study, however with lower improvement, Heinrich et al (2012) showed that, after eight weeks of FMT intervention, the functional circuit training group presented greater efficacy compared to the traditional training of physical readiness of the Army.…”
Section: Discussionmentioning
confidence: 85%
“…Some studies have indicated significant improvements in military personnel after undergoing MPT sessions in upper limbs endurance, corroborating that military training with an approximate duration of eight weeks promotes important adaptations in physical fitness (Campos et al, 2017;De Avila et al, 2013;El Hage & Reis Filho, 2013;Heinrich et al, 2012;Ojanen et al, 2020). Similar to the present study, however with lower improvement, Heinrich et al (2012) showed that, after eight weeks of FMT intervention, the functional circuit training group presented greater efficacy compared to the traditional training of physical readiness of the Army.…”
Section: Discussionmentioning
confidence: 85%
“…On the other hand, the workload of the training period does not seem to have been sufficient to significantly evolve this variable with the male sex. It was observed that the functional activities and the same physical training for both sexes cooperated more effectively for the evolution of the female lean mass, because the female effort to perform the task was probably greater due to the physiological differences between the men [20]. In agreement with the greater effort of women in relation to men when they carry out activities with the same external load, according to Nindl, Jones, Van Arsdale, Kelly and Kraemer [1], young adult males haveapproximately 50% more muscle mass of the upper limbs and 30% more mass lower limb muscle.…”
Section: Discussionmentioning
confidence: 99%
“…These results are supported by studies that report that muscle fitness training promotes increased strength, muscle mass, BMD, BMC and bone resistance to physical stress. Such benefits are important to prevent bone loss throughout life [18,[20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity has the most significant effect on bone status in men Kopiczko et al (2020). After 7 months of training, there was a significant increase in Bone Mineral Content (BMC) and Bone Mineral Density (BMD) (de Avila et al, 2019). Exercise promotes remodeling changes by increasing bone formation by bone osteoblasts through direct and indirect effects.…”
Section: Introductionmentioning
confidence: 99%